Optimal Cluster Head selection in Wireless Sensor Networks using Integer Linear Programming Techniques - Zahra Eskandari; Seyed Amin Hosseini Seno; Muhamed Shenify; Rahmat Budiarto (International Journal of Informatics and Communication Technology (IJ-ICT), 2014)
Wireless sensor network (WSN) consists of sensor nodes which are deployed in the environment densely and randomly. The main constraint of these nodes is limited energy resources, so, the operations which are performed in the network, must be energy efficient. For this reason, routing and data transmission in these networks perform hierarchically and in multi hop manner. One of these hierarchical architectures which have a considerable positive effect on energy consumption is clustering algorithm. But what is important is that the cluster heads election should be done efficiently. Recently some works have focused on optimal cluster head election using Integer Linear Programming techniques. In this paper, Integer Linear Programming techniques are used to formulate the clustering problem.  At first, by using Integer Linear Programming techniques, a scalable and multi objective model for optimal cluster head selection is presented and then the distributed clustering algorithm is proposed. As shown in simulation results, the proposed clustering algorithm is more efficient in terms of energy vs. LEACH algorithm.